Suicidal behavior as a result of maladjustment of servicemen to the conditions of military service in Ukraine - Mykhalchuk, Nataliia; Pelekh, Yurii; Kharchenko, Yevhen; Ivashkevych, Eduard; Zukow, Walery; Ivashkevych, Ernest; Yatsjuryk, Alla (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">ntroduction and aim. The purpose of the article is to analyze the peculiarities of suicidal behavior as a result of maladjustment of servicemen to the conditions of military service in Ukraine. The tasks of the article are to identify among militaries: 1) the most significant risk factors for autoregressive and suicidal behavior; 2) the psychological peculiarities of adaptive disorders that may lead to suicide; 3) protective factors against autoregressive and suicidal behavior. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. To solve the problem of our research, a set of methods was used: theoretical methods – theoretical and methodological analysis of scientific sources, their systematization, classification, generalization; empirical methods – the observation, the interview, a questionnaire, testing, the method of expert assessments. In general 420 militaries were participated in our research. The participants of the 1st stage of the study were 240 militaries in the age 18-25 years old with suicidal and auto-aggressive behavior in anamnesis and one or more attempts of suicide. These militaries were treated in the psychiatric hospital № 1 in Kyiv (Ukraine). At the 2nd stage of the study 180 militaries were participated. They were treated in the Main Military Clinical Hospital (the Center), Kyiv, Ukraine. The research was organized during May–November, 2021. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. We investigated that 120 militaries had various forms of post-suicidal encephalopathy, such as acute affective, non-psychotic state. The number of patients with residual psychoorganic pathology was 41 people (34.16%); after poisoning there were 37 people, the number of patients with toxic encephalopathy – 33 people (27.5%); after self-arson – 9 people, there were 4 patients (3.33%) with burn encephalopathy. We identified the following clinical variants of depressive reactions as a result of maladjustment and suicidal attempts: 1) the reaction of disadaptation in combination with neurosis-like disorders (48.9%); 2) the reaction of maladjustment including hypochondriacal inclusions (in 23.4% of cases of respondents); 3) maladaptive reactions with an anxious component were observed in 28.6% of cases. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. It was shown that the suicidal behavior of soldiers depended on many external and internal risk factors. We showed protective factors against autoregressive and suicidal behavior.